2003
DOI: 10.1016/s1015-9584(09)60375-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Venous Thromboembolism in Asia: A Critical Appraisal of its Incidence

Abstract: While there is a wide variation in the incidence of DVT and VTE as reported in the Asian population, these diseases are by no means rare. The wide variation could be due to the study designs, heterogeneity of the procedures performed and the application of different diagnostic criteria. Results based on prospective studies with objective diagnostic criteria confirm the incidence of VTE as common. Routine chemoprophylaxis must be seriously considered in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
1
30
1
Order By: Relevance
“…The only other similar review by Liew and colleagues 40 from Malaysia comprised 12 studies with a total population of 1495. The lack of deaths from PE was also reported in an Asian multinational study of 407 patients by Piovella and co-workers 34 , where the single death (0·2 per cent) was from cerebral embolism.…”
Section: Discussionmentioning
confidence: 99%
“…The only other similar review by Liew and colleagues 40 from Malaysia comprised 12 studies with a total population of 1495. The lack of deaths from PE was also reported in an Asian multinational study of 407 patients by Piovella and co-workers 34 , where the single death (0·2 per cent) was from cerebral embolism.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The metabolic syndrome may be a common risk factor for VTE in Asian and in whites and may at least partially explain the observed increase in the rate of VTE in Asian patients. 9,18 Recently, two similar population-based cohort studies aimed to clarify the nature of the association between atherosclerosis and VTE. 19,20 In these studies, the authors demonstrated that subclinical atherosclerosis itself is not a risk factor for VTE.…”
Section: Jang Et Al Metabolic Syndrome and Vte In Korean Patients 313mentioning
confidence: 99%
“…While reported overall VTE prevalence in Asian populations has generally appeared lower than in Caucasians, evidence from numerous studies indicates that VTE is certainly not uncommon [7,[11][12][13][14], with incidence, especially among high-risk patient groups, that may not be dissimilar to that in Caucasians [8,[15][16][17][18][19][20].…”
Section: Pe Epidemiology and Trends In Pacific Asiamentioning
confidence: 99%